AN ETHICAL DIMENSION TO DISCIPLINE AND TEACHERS’ USE OF POWER - Osawaru, Arasomwan Endurance; Omatseye, B O J (Sokoto Educational Review, 2017)
Schools have rules and codes of conduct that students are expected to abide by and respect. But when students go against these, and break the rules, then discipline becomes imperative. The implication is that rules and codes of conduct have ethical implications, where ethics is concerned with how a moral person ought to behave. In this same vein, it is expected that in disciplining, teachers should take an ethical posture. This defines who the moral person is. In essence, a teacher who has to enforce discipline must firstly make ethical decisions on it. In this regard, ethical decision making requires more than a belief on the importance of ethics of discipline, it also requires ethical sensitivity.